Association between physical activity level and ankle-branchial index in patients with risk factors of peripheral arterial disease - Hanna Agnieszka Juchniewicz; Anna Lubkowska (Kazimierz Wielki University, 2019)
Introduction: Peripheral arterial disease (PAD) causes a three-fold increase in risk of mortality and major cardiovascular events. PAD is typically diagnosed with ankle-branchial index (ABI) ≤0.90. World Health Organization recommends to address behavioural risk factors to prevent further burden of cardiovascular diseases. Purpose: The aim of this study was to examine correlation between physical activity level and ABI among patients with risk factors of PAD and ABI in normal range or ABI indicating some or moderate arterial disease. Methods: 71 patients who were over 65 years old and had minimum of two additional PAD risk factors were recruited. Physical activity level was measured by International Physical Activity Questionnaire, walking ability was assessed by 6-minute Walking Test (6MWT). Results: Mean ABI was in normal range (1.08, SD 0.15). Mean Body Mass Index of the group indicated obesity (30.6, SD 5.5 kg/m2). Among modifiable PAD risk factors, hypertension and dyslipidaemia were the most prevalent. Most of the participants (62%) were moderately active. Mean total physical activity was 5310.2 MET-min per week. The average person has been sitting for around 5 hours per day. The mean result of 6MWT was 432.2 meters (SD 103.4). Following correlations were observed: between total physical activity level and ABI (r=0.17), between walking ability and ABI (r=0.39), sitting time and ABI (r=-0.32). Conclusions: older people with PAD risk factors could benefit from everyday walking and housework. Incorporating walking while transportation can exert PAD prevention effect. Sitting time should be avoided. These recommendations apply not only for patients with some or moderate PAD, but also for older individuals with normal range ABI, but with PAD risk factors.